THE LOCAL COMMUNITY UNDERSTANDING OF THE FACTORS INFLUENCING THE DECLINE OF SANINTEN (CASTANOPSIS ARGENTEA (BLUME) A.DC.) AND TUNGURUT (CASTANOPSIS TUNGURRUT (BLUME) A.DC.) IN THE BUFFER VILLAGES OF THE GUNUNG HALIMUN-SALAK NATIONAL PARK - ELBIBIYA IZZUL PENIDDA; UMARI JUMARI; KARYADI BASKORO; DENI SAHRONI; PENIWIDIYANTI PENIWIDIYANTI; WAWAN SUJARWO (BRIN Publishing (Penerbit BRIN), 2024)
Saninten (Castanopsis argentea) and tungurut (Castanopsis tungurrut) are plant species belonging to the family Fagaceae, native to the mountainous forest ecosystem within the Gunung Halimun-Salak National Park (GHSNP). These species are currently classified as endangered according to the IUCN Red List due to their significance in providing seeds for consumption and wood for construction materials. This research aims to examine the local community’s knowledge concerning the presence, scarcity, and underlying causes of the decline of both species in the buffer villages of GHSNP. In this study, we employed survey methods and semi-structured interviews conducted with various informants. The data collected were meticulously described and analyzed descriptively. The findings revealed that the local community, in general, holds knowledge about the scarcity of species primarily based on field observations rather than legal or conservation status. Currently, both species are challenging to locate in the buffer villages of the GHSNP. According to the local community’s knowledge, the causes of species scarcity can be categorized into internal and external factors. Internal factors include both species having a slow natural regeneration pattern, difficulties in germination, and vulnerability of seedlings to environmental conditions. Meanwhile, external factors encompass seed and timber exploitation, habitat loss, climate changes, limited knowledge, skills, and understanding of forest plants, and the current perception among locals that C. argentea and C. tungurrut offer limited economic benefits, leading to the gradual neglect of these species’ existence.